EKSISTENSI UNDANG-UNDANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA DALAM AKTUALISASI KONSEP NUSYUZ FIQH MADANI - Handayani, Tutik (Jurisdictie: Jurnal Hukum dan Syariah, 2012)
The most potential victims of domestic violence are women. it is happened due to several reasons. One of the reasons is nusyuz practice by hitting the wife as the alternative of nusyuz solution as has been understood in Quran. The verse, then, is legitimized by classical product of fiqh. If we discuss further, that understanding need to be reinterpreted since its relevance with the implementation of domestic violence regulation Number 23, 2004 which issues the ban of domestic violence. The objective of this writing is to discuss again the concept of nusyuz in classical fiqh which tends to give bigger portion to men and to subordinate women in nusyuz case. At the end of this writing, it is known that nusyuz in classical fiqh less accommodate the principles of gender equity. Therefore, it is a need for re-understanding the concept in line with theimplementation of domestic violence regulation.   Korban kekerasan dalam rumah tangga yang paling rentan adalah perempuan. Hal ini terjadi karena berbagai alasan. Diantaranya ialah penyelesaian nusyuz istri dengan cara memukulnya yang mana alternatif tersebut dipahami dari Al-Qur’an. Kemudian ayat tersebut dilegitimasi oleh produk fiqh klasik. Jika ditelaah lebih lanjut, pemahaman tersebut membutuhkan reinterpretasi karena relevansinya dengan keberlakuan UU RI PKDRT No. 23 tahun 2004 yang mendengungkan tentang larangan ke- kerasan dalam rumah tangga. Tulisan ini bertujuan untuk mendiskusikan kembali konsep nusyuz dalam fiqh klasik yang terkesan memberikan porsi lebih kepada laki-laki dan mensubordinasikan perempuan dalam permasalahan nusyuz. Pada bagian akhir penelitian ini diketahui bahwa nusyuz dalam fiqh klasik kurang mengakomodir prinsip-prinsip kesetaraan gender. Sehingga perlu pemahaman kembali dengan diberlakukannya UU PKDRT.